Racial and textual translation through signifyin(g) and eshu in Ika Hügel-Marshall’s Invisible Woman: Growing Up Black in Germany (2008) - Martins, José Endoença (Research Journal in Advanced Humanities, 2020)
This study outlines the “call and response” process, by means of which African-German Ika Hügel-Marshall’s (2012) autobiography Daheim unterwegs: Ein deutsches Leben and its English version Invisible Woman: Growing up Black in Germany (2008) establish translational dialogues through both interraciality and intertextuality. Racially, both entanglement and separation between white Germany and black America is under analysis; linguistically, both disentanglement and harmony between German and English languages invites study. The emphasis on interraciality and intertextuality helps us see translation as conversation between two racialized worlds (Germany/USA) and two specific literary products (source/target texts). The analysis of Marshall’s translation highlights her dealing with black and white values, through the notions Negriceness, Negritude and Negriticeness; the study of the narrative’s rendition emphasizes manipulations of source and target languages through the concepts Paralatio, Similatio and Translatio.